P–514 RAN-Translation in Fragile X associated Premature Ovarian Insufficiency (FXPOI): FMRpolyG as a predictive tool. (6th August 2021) - Nguyen, X P; Messmer, B; Dietrich, J E; Hinderhofer, K; Strowitzki, T; Rehnitz, J
Abstract: Study question: Does repeat-associated non-AUG (RAN) translation lead to accumulation of polyglycine- containing protein (FMRpolyG) in human lymphocytes and mural granulosa cells of FMR1 premutation carriers? Summary answer: Lymphocytes and granulosa cells from FMR1 premutation carriers contain intracellular inclusions that stain positive for both FMRpolyG and ubiquitin. What is known already: Fragile-X-associated-Primary-Ovarian-Insufficiency (FXPOI) is characterized by oligo/amenorrhea and hypergonadotropic hypogonadism associated with the expansion of CGG-repeats in the 5'UTR of FMR1, called premutation (PM) (n: 55–200). Approximately 20% of women carrying a FMR1-premutation (PM) allele develop FXPOI. RAN-translation dependent on variable CGG-repeat length is hypothesized to cause FXPOI due to the production of a polyglycine-containing FMR1-protein, FMRpolyG. Recently, FMRpolyG inclusions were found in neuronal brain cells of FXTAS patients and stromal cells of the ovary of an FXPOI patient. Study design, size, duration: Lymphocytes and granulosa cells (GCs) from women with PM (6) and women without PM (10) (controls) were analyzed by immunofluorescence (IF) staining for the presence of inclusions positive for ubiquitin and FMRpolyG. Cell lysis and protein extraction samples were subjected to Fluorescent Western Blot (WB) analysis to detect FMRP and FMRpolyG Participants/materials, setting, methods: Human GCs were obtained from follicular fluid after oocyte retrieval and lymphocytes were isolated from peripheral blood using Ficoll-Paque. Cells suspended in PBS were adhered to a glass-coverslip placed at the bottom of the 6-well culture plate, via gravity sedimentation. Adhered cells were fixed, IF staining for FMRpolyG and ubiquitin was performed and analyzed by fluorescence microscopy. Fluorescent WB was used to demonstrate the expression of FMRP, FMRpolyG in extracted protein from lymphocytes and GCs. Main results and the role of chance: FMRP was successfully detected by fluorescence WB in both lymphocytes and GCs. FMRP is mainly present in cytoplasm and was expressed in greater amount in GCs than in leukocytes. Moreover, FMRP expression was significantly decreased in GCs from FMR1-PM compared with controls. Lymphocytes from PM-carriers and controls were immunostained for FMRpolyG and ubiquitin. In PM-carriers, FMRpolyG was present as aggregates, whereas in controls only a weak signal without inclusions was detectable. The expression pattern of FMRpolyG in GCs was similar to that in lymphocytes with a significant increase in PM-carriers. There, the FMRpolyG-aggregates additionally demonstrated as ubiquitin-positive inclusions. These may resemble the toxic potential of these protein fractions involved the ovarian damage in developing FXPOI. Limitations, reasons for caution: More patients are needed to support the present findings. Further investigation into the possible consequences of these FMRpolyG-positive inclusions in PM-carriers is also advisable. Wider implications of the findings: We found for the first time FMRpolyG-accumulation in lymphocytes and GCs from FMR1-PM-carriers in ubiquitin-positive inclusions. Future experiments evaluating consistency in more patients and elucidating the impact on fertility and prospective value for individual ovarian reserve are therefore in preparation. Trial registration number: Not applicable